Prasa parafialna w diecezji zielonogórsko-gorzowskiej. Rekonesans badawczy = Parish Press in the Diocese of Zielona Góra and Gorzów. Reconnaissance research - Wasilewski, Krzysztof (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
This article presents the state of the parish press in the Diocese of Zielona Góra and Gorzów, both quantitatively and qualitatively. The analysis is based on previous studies of the subject, as well as on the author`s own research. Apart from the printed press, other forms of media activity in the parish, such its internet presence, are also studied. As indicated in the analysis, the internet provides a convenient tool for the parish to provide important information and opinions. In some cases, one could mention the phenomenon of convergence, where the printing press and the internet complement one another.
Keywords: badania naukowe; prasa; prasa parafialna; prasoznawstwo; diecezja zielonogórsko-gorzowska; konwergencja; internet; scientific research; press; parish press; press studies; Zielona Góra-Gorzów Diocese; convergence